Beyond VNFM: Filling the gaps of the ETSI VNF manager to fully support VNF life cycle operations. Issue 5 (11th April 2019) - Venâncio, Giovanni; Garcia, Vinícius Fulber; da Cruz Marcuzzo, Leonardo; Tavares, Thales Nicolai; Franco, Muriel Figueredo; Bondan, Lucas; Schaeffer‐Filho, Alberto Egon; Paula dos Santos, Carlos Raniery; Granville, Lisandro Zambenedetti; P. Duarte, Elias
Summary: One of the main challenges to use network functions virtualization (NFV) is to properly manage the life cycle of the virtualized network functions (VNFs). Current solutions based on the ETSI standard NFV architectural framework are complex and require the knowledge of a myriad of details of the underlying infrastructure. This work proposes a VNF manager (VNFM) specification that supports different platforms and VNF utilization scenarios. The proposed VNFM specification defines a set of APIs, modules, and components, for both the end user and the back‐end that provide the fundamental set of operations required to fully manage the VNF life cycle. Our primary goal is to simplify the operations, in particular reducing the need for the network operator to know the details of the virtualized infrastructure. Note that the proposed solution fills a gap and complements the ETSI VNFM module. A prototype was implemented, and experimental results show the effectiveness and low overhead of the proposed solution. Abstract : One of the main challenges to use network functions virtualization (NFV) is to properly manage the life cycle of the virtualized network functions (VNFs). This work proposes a VNF manager (VNFM) specification that supports different platforms and VNF utilization scenarios. The proposed VNFM specification provides the fundamental set of operations required to fully manage the VNF life cycle. Our primary goal is to simplify the operations, reducing the need for the network operator to know the details of the virtualized infrastructure.